К вопросу о лексических заимствованиях, их межъязыковом и межкультурном потенциале в условиях обучения русскому языку как второму и следующему иностранному языку (на материале лексических галлицизмов в русском языке) - Vicaire, Xenie (Studia Rossica Posnaniensia, 2014)
This article is devoted to analyzing lexical Gallicisms in the Russian language based on which a potential Russian-French interlanguage and intercultural parallels are formed. The author defines the theoretical context of lexical borrowing, which is one of the ways of enriching a language’s lexicon. It also focuses on several possibilities of using these parallels, which can contribute to optimizing the teaching process and its effectiveness. The article shows how this phenomenon can help in developing the compensatory competence that students already have and to form intercultural competence under the conditions of multilingual language acquisition.